Bio Plastics from Biomass - Leao, Alcides L. [UNESP]; Cesarino, Ivana [UNESP]; de Souza, Milena C. [UNESP]; Moroz, Ivan [UNESP]; Jawaid, Mohammad (Wiley, 2024)
Plastics represent a huge issue nowadays in terms of pollution and/or contamination in water bodies, soils, and air. Bioplastics were developed aiming to mitigate and/or solve the problem of inadequate disposal or low value for recycling of plastic wastes and rejects generated in packaging, agriculture, livestock, forestry, agro-industrial, and routine activities. The environmental impact of improperly disposed plastics and their consequences on the human, animal, and environmental food chain are clear, and actions toward the use of more environmentally friendly materials are a must. The presence of microplastics in the ocean and, more recently, in the food chain is a result of inadequate plastic use or disposal. The bioplastics, derived from biobased polymers, may provide a solution. Nevertheless, it is important to consider the whole cycle of bioplastics, their properties, and how they compare to their chemical synthetic counterparts available nowadays.
Keywords: agri wastes; bioplastics; biopolymers; circular economy; residues